Hydrogel Sensors and Actuators Engineering and Technology - Gerlach, Gerald.; Arndt, Karl-Friedrich. (Springer Series on Chemical Sensors and Biosensors, Methods and Applications, 2010)
Hydrogels are a fascinating class of polymers which show an immense ability of swelling under the influence of temperature, pH value or concentrations of different species in aqueous solutions. The volume change can amount up to several hundred percent. This unique behaviour is already used in such applications like disposable diapers, contact lenses or drug-delivery systems. The ability to perform mechanical work has been shifted the technical interest more and more towards sensors and actuators exploiting the thermo-chemo-mechano-electrical coupling within hydrogels. The accuracy requirements for such devices are much more demanding than for previous applications. Therefore, a deep knowledge of both the material and the functional properties of hydrogel sensors and actuators is needed. The monograph describes state-of-the-art and recent developments for these materials in sensor and actuator technology.